The “quality” and “quantity” of microbial species drive the degradation of cellulose during composting - Chen, Xiaomeng; Cheng, Wanting; Li, Shenzhou; Tang, Xiaofei; Wei, Zimin (Bioresource technology, 2021)
[Display omitted] •The degradation degree of cellulose could be explained by cellulases activities.•The cellulose degradation needed the cooperation of various microorganisms.•The microbial evenness and richness were found to be the primary driving factors.•The richness symbolized the “quality” of microbial species.•The evenness symbolized the “quantity” of microbial species. The aim of this study was to explore the contribution of microbial community to cellulose degradation during cellulosic wastes composting. Three raw materials with different cellulose content were employed, including rice straws (RS), leaves (L) and mushroom dregs (MD). The cellulose degraded by 92.09%, 56.68% and 40.03% during RS, L and MD composting, respectively, which could be explained by cellulases activity. Besides, each cellulase were only linked to a specific group of bacteria, thus cellulose degradation needed the cooperation of various microorganisms. Ultimately, structural equation models verified that the richness and evenness of microbial community were the primary driving factors of cellulose degradation. The richness symbolized microbial functionality, which was equivalent to the “quality” of microbial species. The evenness symbolized the scope of function, which was equivalent to the “quantity”. Therefore, the “quality” and “quantity” of microbial species drove cellulose degradation during RS, L and MD composting.